Recent changes observed in column ozone concentrations over India (MAUSAM, 2000)
Ozone observations taken during the past 23-39 years by Dobson Spectrophotometers at Delhi, Varanasi, Pune and Kodikanal have been analysed to examine its long-term trend over Indian stations. An increasing trend of this species over the years has been noticed at all the places, except at Varanasi, where a decreasing trend has been found. The cause of these trends could be attributed, partly, to the trends of ozone in the troposphere. The results also indicate that there are certain recent changes in ozone levels at the Indian stations. These changes are less apparent in long-term trend analysis of total ozone data as the increase in tropospheric ozone has a compensating effect to the decrease in ozone at stratospheric levels.